Genetic diversity of X-STR markers in Jat Sikh population of Punjab, India and its comparison with other 39 global populations. (3rd July 2020) - Kakkar, Sonia; Shrivastava, Pankaj; Sahajpal, Vivek; Sharma, Arun; Devi, Nisha; Mandal, S. P.; Kumawat, R. K.
Abstract: Background: The Jat Sikh population is the largest endogamous group of Punjab, a state in north-west India, and has not yet been explored for genetic polymorphism based on X-STR genetic markers. In India, which is the second most populous country in the world, only two population studies based on X-STR markers have been reported so far. Aim: To explore the genetic diversity of 12 X chromosomal STR genetic markers in the Jat Sikh population of Punjab and expand the X-STR polymorphism database. Subjects and methods: In this study, a total of 200 Jat Sikh individuals (100 males and 100 females) residing in Punjab were investigated for 12 X-STR markers using the Investigator Argus X-12 QS Kit. Results: The highest power of discrimination (PD) in females (PDf ) and males (PDm ) was observed to be 0.965 (DXS10135) and 0.929 (DXS10135 and DXS10148), respectively. DXS10135 was found to be the most polymorphic and discriminating locus among all the studied loci in both males and females with highest values of power of discrimination (PD) and polymorphic information content (PIC) as well. Conclusion: Overall, the studied markers of the Argus 12 X-STR kit provide high polymorphic information which may prove to be an important tool in resolving issues such as missing person identification, incest, immigration disputes, kinship analysis and genealogical studies. The dataset obtained from this study will add to the present database of X-STRs.